Peningkatan Pemahaman Dasar Akuntansi Mahasiswa melalui Penerapan Direct Instruction Dengan Media Worksheet - Riski Ayu Arnila; Hidayatul Ahyani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The aim of this study is to improve students' basic understanding of accounting by using the Direct Instruction (DI) model on financial statement materials using worksheet media. This research is action research with research subjects of Accounting Education students at Gunung Rinjani University. Data collection techniques by observation, interviews, documentation and tests. While the data analysis technique used is quantitative and qualitative data analysis, the combination method used is a convergent parallel mixed method. The results indicate that implemantation of Direct Instruction (DI) model with worksheet media can improve students' basic understanding of accounting. The increase in students’ basic understanding is shown by various changes in students’ abilities in terms of students' abilities in preparing income statements, preparing Statement of Retained Earnings, and students' abilities in preparing balance sheet. The increase in students' basic understanding of accounting in this study was also marked by an increase in the average value of basic accounting understanding, the average value of students from 20.00 before receiving the action to 49.33 after receiving the action in cycle 1 and increasing again to 80.67 after receiving the action. in cycle 2 and increased to 84.33 in cycle 3. In cycles 2 and 3, 93.33% of students succeeded in increasing their basic understanding of accounting.